Growing Pains: Socioeconomic Constraints and Students Coping Strategies in Nigerian Universities - Longe, Joshua Sunday; Igbinomwanhia, Osasere Greg (NIU Journal of Social Sciences, 2026)
The Nigerian universities is fast becoming boiling pots for students rather than a melting pots of decent academic enterprise and intellectualism where the human mind can be forged into dexterously skilful individuals. The likelihood that students will experience this reality is however froth with threats. This paper develops a prototypical conclusive causality in the Nigerian universities and highlights the issues of socio-economic constraints; the challenges it poses for students and the various coping strategies they deployed to survive. The study uses a mix method with a survey of 368 students. Inadvertently, results show that student experience constraints most of which bothers on economic matters and inabilities. To contest their estate, student often employ social support systems and work part job where opportunity avails in-order to cope. The study reveal that constraints induce anxiety that affects student overall welfare and suggest a student’ centred government interventions support programme, a vibrant university scholarship and a wider university economic reform programmes. Keywords: Constraint, University, Socioeconomic, Student, Survival/Coping strategy.